Genome-wide identification and evaluation of constitutive promoters in streptomycetes - Li, Shanshan (Microb Cell Fact, 2015)
BACKGROUND: Streptomycetes attract a lot of attention in metabolic engineering and synthetic biology because of their well-known ability to produce secondary metabolites. However, the available constitutive promoters are rather limited in this genus. RESULTS: In this work, constitutive promoters were selected from a pool of promoters whose downstream genes maintained constant expression profiles in various conditions. A total of 941 qualified genes were selected based on systematic analysis of five sets of time-series transcriptome microarray data of Streptomyces coelicolor M145 cultivated under different conditions. Then, 166 putative constitutive promoters were selected by following a rational selection workflow containing disturbance analysis, function analysis, genetic loci analysis, and transcript abundance analysis. Further, eight promoters with different strengths were chosen and subjected to experimental validation by green fluorescent protein reporter and real-time reverse-transcription quantitative polymerase chain reaction in S. coelicolor, Streptomyces venezuelae and Streptomyces albus. The eight promoters drove the stable expression of downstream genes in different conditions, implying that the 166 promoters that we identified might be constitutive under the genus Streptomyces. Four promoters were used in a plug-and-play platform to control the expression of the cryptic cluster of jadomycin B in S. venezuelae ISP5230 and resulted in different levels of the production of jadomycin B that corresponded to promoter strength. CONCLUSIONS: This work identified and evaluated a set of constitutive promoters with different strengths in streptomycetes, and it enriched the presently available promoter toolkit in this genus. These promoters should be valuable in current platforms of metabolic engineering and synthetic biology for the activation of cryptic biosynthetic clusters and the optimization of pathways for the biosynthesis of important natural products in Streptomyces species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-015-0351-0) contains supplementary material, which is available to authorized users.